2018
DOI: 10.1111/jori.12250
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Selection in an Ancillaries Health Insurance Market

Abstract: I study two important aspects of the Australian private ancillaries health insurance (PAHI) market-moral hazard and self-selection. PAHI covers out-of-hospital health services including dental, optometry, physiotherapy, and chiropractic. Using instrumental variables methods, I find evidence that PAHI increases utilization, particularly for dental, physiotherapy, chiropractic, osteopathy, and acupuncture. I also find evidence of selection effectsboth adverse and favorable. Several variables jointly predict a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…age, education, sex, employment status, insurance status, risk preferences, household composition, self-assessed health and regional indicators (see Appendix Table A1 for a complete list of variables and definitions). Previous work has established that many of these controls predict hospitalizations [ 27 , 28 ] and ancillary health service utilization [ 29 ], particularly age, gender, income, health and insurance.…”
Section: Datamentioning
confidence: 99%
“…age, education, sex, employment status, insurance status, risk preferences, household composition, self-assessed health and regional indicators (see Appendix Table A1 for a complete list of variables and definitions). Previous work has established that many of these controls predict hospitalizations [ 27 , 28 ] and ancillary health service utilization [ 29 ], particularly age, gender, income, health and insurance.…”
Section: Datamentioning
confidence: 99%
“…Previous work has established that many of these controls predict hospitalizations (see e.g. Buchmueller et al, 2013;Doiron & Kettlewell, 2018) and ancillary health service utilization (Kettlewell, 2019b), particularly age, gender, income, health and insurance.…”
Section: Main Variablesmentioning
confidence: 99%
“…PHI lowers the effective cost of allied health services and private hospital care, inducing individuals to consume more of these services (Doiron & Kettlewell 2018;Kettlewell 2018;Meng et al 2017;Savage & Wright 2003). This could improve health status, if the marginal effect of this care is positive.…”
Section: Mechanismsmentioning
confidence: 99%
“…Such services, since typically more discretionary than hospital procedures, may be associated with an even larger moral hazard effect. Kettlewell (2018) instrumented private ancillaries insurance with an indicator for whether an individual wore glasses or contact lenses. He found that PHI increased utilisation of dental, physiotherapy, osteopathy, chiropractic and acupuncture services, and weaker evidence for a positive effect on mental health and naturopathy services.…”
Section: Australian Literaturementioning
confidence: 99%
See 1 more Smart Citation